Natural Products as Lead Compounds for Sodium Glucose Cotransporter (SGLT) Inhibitors - Blaschek, Wolfgang (Planta Medica, 2017)
Glucose homeostasis is maintained by antagonistic hormones such as insulin and glucagon as well as by regulation of glucose absorption, gluconeogenesis, biosynthesis and mobilization of glycogen, glucose consumption in all tissues and glomerular filtration, and reabsorption of glucose in the kidneys. Glucose enters or leaves cells mainly with the help of two membrane integrated transporters belonging either to the family of facilitative glucose transporters (GLUTs) or to the family of sodium glucose cotransporters (SGLTs). The intestinal glucose absorption by endothelial cells is managed by SGLT1, the transfer from them to the blood by GLUT2. In the kidney SGLT2 and SGLT1 are responsible for reabsorption of filtered glucose from the primary urine, and GLUT2 and GLUT1 enable the transport of glucose from epithelial cells back into the blood stream.The flavonoid phlorizin was isolated from the bark of apple trees and shown to cause glucosuria. Phlorizin is an inhibitor of SGLT1 and SGLT2. With phlorizin as lead compound, specific inhibitors of SGLT2 were developed in the last decade and some of them have been approved for treatment mainly of type 2 diabetes. Inhibition of SGLT2 eliminates excess glucose via the urine. In recent times, the dual SGLT1/SGLT2 inhibitory activity of phlorizin has served as a model for the development and testing of new drugs exhibiting both activities.Besides phlorizin, also some other flavonoids and especially flavonoid enriched plant extracts have been investigated for their potency to reduce postprandial blood glucose levels which can be helpful in the prevention and supplementary treatment especially of type 2 diabetes.
Keywords: Malus domestica; Rosaceae; Phlorizin; flavonoids; SGLT-inhibitors; gliflozins; diabetes